KINERJA PEGAWAI DI DINAS PENDIDIKAN KABUPATEN PASAMAN BARAT - Ananda Rista, Tiwi; Susanti, Lusi; Achyar, Novriyanti; Ginanjar, Singgih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This research is motivated by problems found related to employee performance at the West Pasaman Regency Education Office. The purpose of this study is to obtain information and describe employee performance at the West Pasaman Regency Education Office. This type of research uses a descriptive quantitative approach. The population of this study was 64 employees at the West Pasaman Regency Education Office, with a sample of 57 employees selected through proportional random sampling techniques. The research instrument used was a Likert scale questionnaire with five answer choices that have been tested for validity and reliability. The results show that employee performance at the West Pasaman Regency Education Office is in the high category with an average score of 4.20 and an achievement percentage of 84%. These findings indicate that the majority of employees have demonstrated the ability to complete work according to targets, high responsibility, and the quality of work results in accordance with established standards.